Examining the barriers and recommendations for integrating more equitable insomnia treatment options in primary care - Vargas, Ivan; Egeler, Mara; Walker, Jamie; Benitez, Dulce Diaz (Frontiers in Sleep, 2023)
Chronic insomnia is the most common sleep disorder, occurring in approximately 32 million people in the United States per annum. Acute insomnia is even more prevalent, affecting nearly half of adults at some point each year. The prevalence of insomnia among primary care patients is even higher. The problem, however, is that most primary care providers do not feel adequately knowledgeable or equipped to treat sleep-related concerns. Many providers have never heard of or have not been trained in cognitive behavioral therapy for insomnia or CBT-I (the first line treatment for insomnia). The focus of the current review is to summarize the factors contributing to why sleep health and insomnia treatment have been mostly neglected, identify how this has contributed to disparities in sleep health among certain groups, particularly racial and ethnic minorities and discuss considerations or potential areas of exploration that may improve access to behavioral sleep health interventions, particularly in primary care.